2006
DOI: 10.2105/ajph.2004.049502
|View full text |Cite
|
Sign up to set email alerts
|

The Garden of Eden: Acknowledging the Impact of Race and Class in Efforts to Decrease Obesity Rates

Abstract: Geographic assessments indicate that the selection of produce in local supermarkets varies by both area-level income and racial composition. These differences make it particularly difficult for low-income African American families to make healthy dietary choices. The Garden of Eden produce market was created to improve access to high-quality, affordable produce for these communities. The Garden of Eden is housed in a church in an economically depressed African American community in St Louis, Mo, that has less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 10 publications
2
20
0
Order By: Relevance
“…This result corroborates the findings of several studies examining the neighborhood food environment [1,13]. Still, few grocery stores carried more than 50% of the culturally specific fruits and vegetables assessed.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result corroborates the findings of several studies examining the neighborhood food environment [1,13]. Still, few grocery stores carried more than 50% of the culturally specific fruits and vegetables assessed.…”
Section: Discussionsupporting
confidence: 89%
“…The researchers found that although culturally relevant fruits and vegetables such as collard greens and okra were more costly than other commonly consumed fruits and vegetables, they were more likely to be found in the homes of African-American families with school children. Notwithstanding the insights gained from these studies, there remains a paucity of food environment studies specifically exploring fruit and vegetable varieties that may be favored by ethnic or racial minority populations in the US [1,12,13]. This omission in the study of food environments may limit our ability to implement effective population-based policies, as we may not be documenting a critical factor influencing purchasing behaviors and subsequent dietary patterns, particularly for racial and ethnic minority groups [5].…”
Section: Introductionmentioning
confidence: 99%
“…Facilitating access to nutritious foods by using methods such as changing the offerings in vending machines in schools and work sites, 18 improving access to supermarkets and markets that offer increased selection of fruits and vegetables in underserved areas, 19 promoting the consumption of family meals 20 and reducing the amount of money spent on meals outside home 21 are ideas that could contribute to reducing energy intake. Policy approaches include proposals to tax certain foods and beverages and forcing disclosure of nutritional information including caloric content of meals.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] Because disparities exist in access to parks, recreation, and fresh food access, 26,27 some communities have included social justice themes in promoting opportunities for nutritional and activity change.…”
Section: Alternative Frames For Obesitymentioning
confidence: 99%